Agile Processes in Software Engineering and Extreme Programming: 17th International Conference, XP 2016, Edinburgh, UK, May 24-27, 2016, Proceedings - Sharp, Helen; Hall, Tracy (Lecture Notes in Business Information Processing, 2016)
Business Information Systems; Software Engineering; Software Management; Management of Computing and Information Systems